Upper gastrointestinal cancer in its early stages is predominantly asymptomatic. Issue 1 (10th September 2011) - Berrill, James W; Turner, Jeff K; Hurley, Jo J; Swift, Gillian; Dolwani, Sunil; Green, John T
Abstract : Background: Current guidelines for urgent endoscopic investigation of dyspepsia are based on alarm features and age criteria. However, there is concern that this type of guideline may delay the diagnosis of upper gastrointestinal (GI) cancer. Objective: To evaluate the timescale of symptoms in upper GI cancer, determining whether patients experience dyspepsia before developing alarm features, and hence whether the current guidelines may delay diagnosis. Method: A prospective study of patients diagnosed with upper GI cancer between May 2004 and January 2007. A structured interview was performed directly after endoscopic diagnosis regarding the nature and duration of symptoms. Results: Alarm features were present in 56 of the 60 patients interviewed. Only eight patients reported dyspepsia before developing their alarm feature; three of these had complained of dyspepsia for >10 years, one reported dyspepsia preceding the alarm feature by 18 months and in four patients dyspepsia preceded the alarm feature by ≤8 weeks. Preceding dyspepsia did not cause significant delay in referral for endoscopy (p=0.670), or affect tumour stage at diagnosis (p=0.436) or length of survival (p=0.325). Conclusion: It is rare for patients with upper GI cancer to experience significant dyspepsia before the onset of their alarm symptoms, therefore limiting the prospect of an earlier diagnosis. Early upper GI cancer is largely asymptomatic, and guidelines should limit the availability of open-access gastroscopy in simple dyspepsia. Increased awareness of the need to urgently investigate patients with concurrent anaemia or weight loss is required.